Method for preparing high-toughness silicon carbide ceramic material and application
Through chemical vapor deposition technology, the grain size and porosity of silicon carbide ceramic materials are controlled, and the problems of material toughness and purity are solved, and the preparation of high-purity and high-toughness silicon carbide ceramic materials are realized, which is suitable for a variety of application scenarios .
Patent Information
- Application Number
- CN202411113139.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing silicon carbide ceramic materials are prone to fine cracks during processing, resulting in low toughness and brittle fracture. The existing toughening methods will reduce the purity of the material and cannot meet the requirements of high purity for wafer production and etching.
Using chemical vapor deposition (CVD) technology, by controlling the temperature, pressure and gas flow ratio in the deposition furnace, a high-purity silicon carbide ceramic material with a grain size of 100nm~1000nm and a porosity of ≤0.05% was prepared to change the crystal breaking method to improve toughness.
It realizes high purity and high toughness of silicon carbide ceramic materials, adapts to the needs of various application scenarios, improves the material's microcrack resistance and processability, and meets the high purity requirements of wafer epitaxial growth and etching.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, in particular to a method for preparing a high-toughness silicon carbide ceramic material and application thereof. Background Art
[0002] At present, micro cracks are easily generated in the process of preparing silicon carbide blanks, which seriously affects the service life of silicon carbide ceramic materials. Some silicon carbide ceramic materials also have low toughness and may even suffer brittle fracture during processing. Therefore, the development of a silicon carbide ceramic material that can fully exert the excellent performance of silicon carbide materials and have high toughness characteristics is the key to the current silicon carbide ceramic material field.
[0003] In the prior art, the toughening methods for silicon carbide ceramic materials are all focused on using sintering reactions to dope some other metal compounds or organic compounds into silicon carbide ceramic materials, thereby changing the silicon carbide crystal structure, and then achieving the purpose of increasing the toughness of silicon carbide materials. For example, carbon powder, porous carbon materials and hexagonal boron nitride powder and other components are fully mixed, and silicon carbide materials are formed in a high-temperature vacuum furnace by high-temperature hot sintering. For example, in the prior art, there is also a method of using in-situ generation to introduce Ti3SiC2 and TiB2 into the silicon carbide matrix to form a toughening body, thereby improving the toughness of the silicon carbide matrix. However, the above-mentioned toughening technology of introducing impurities will reduce the purity of silicon carbide ceramic materials. The incorporation of many impurity metals greatly limits the application of silicon carbide ceramic materials in wafer production or silicon carbide etching, especially in the process of epitaxial growth of wafers, there are high requirements for the purity of silicon carbide ceramic materials, and metal doping or other element doping cannot meet production needs.
[0004] Therefore, there is an urgent need to develop a new silicon carbide ceramic material that has both high purity and high toughness, so that it can not only meet the high purity requirements of silicon carbide ceramic materials for wafer epitaxial growth or silicon carbide etching, but also use its excellent processability to produce more shapes to meet the needs of various application scenarios. Summary of the invention
[0005] In order to improve the above-mentioned problems existing in the prior art, the present invention provides a method for preparing a high-toughness silicon carbide ceramic material and the application of the high-toughness silicon carbide ceramic material prepared by the method in wafer production or silicon carbide etching. The high-toughness silicon carbide ceramic material prepared by the present invention can have high purity and high toughness, which can not only meet the requirements of high purity of silicon carbide ceramic material for wafer epitaxial growth or silicon carbide etching, but also can make more shapes by using its excellent toughness and processability, so as to meet the needs of various application scenarios.
[0006] In order to achieve the above object, a first aspect of the present invention provides a method for preparing a high-toughness silicon carbide ceramic material, the method comprising the following steps: Step S1, placing the pickled, washed and dried deposition substrate into a deposition furnace, evacuating the furnace, raising the temperature in the deposition furnace to 900° C. to 1800° C., and raising the pressure in the furnace to 10 kPa to 55 kPa; Step S2, using reducing gas as carrier gas to pass carbosilane gas into the deposition furnace of step S1, the gas flow ratio of the reducing gas to the carbosilane gas is 1:(3-120), adjusting the gas valve to maintain the deposition pressure in the deposition furnace stable at 10 kPa-30 kPa, and stabilizing the deposition temperature in the deposition furnace at 1050° C.-1650° C.; Step S3: After the chemical vapor deposition is completed, the gas in step S2 is stopped, and the high-toughness silicon carbide ceramic material is formed on the surface of the deposition substrate; The grain size of the high-toughness silicon carbide ceramic material is 100nm-1000nm, and the apparent porosity of the high-toughness silicon carbide ceramic material is ≤0.05%.
[0007] The second aspect of the present invention provides the use of a high-toughness silicon carbide ceramic material prepared by the method described in the first aspect of the present invention in wafer production or silicon carbide etching.
[0008] Through the above technical solution, the present invention has at least the following advantages compared with the prior art: (1) The high-toughness silicon carbide ceramic material prepared by the method provided by the present invention can give the silicon carbide ceramic material better microcrack resistance by controlling the grain size and apparent porosity of the silicon carbide ceramic material within a suitable range, thereby effectively improving the toughness of the silicon carbide ceramic material, thereby enabling the silicon carbide ceramic material to better adapt to the commonly used processing methods on the market, and further enabling the production of silicon carbide ceramic materials with more different shapes that meet various application scenarios.
[0009] (2) The preparation method of the high-toughness silicon carbide ceramic material provided by the present invention adopts a chemical vapor deposition (CVD) process. During the preparation process, no other metals or organic compounds are doped. The purity of the prepared silicon carbide ceramic material is relatively high, which can reach 99.9999%, and can better meet the high-purity requirements of silicon carbide in the epitaxial growth process of wafers.
[0010] (3) The method for preparing high-toughness silicon carbide ceramic materials provided by the present invention can adjust the deposition pressure and deposition temperature in the deposition furnace, as well as the gas flow ratio of the reducing gas and the carbon silane gas on the basis of the chemical vapor deposition preparation process, so that the prepared silicon carbide ceramic material can form a suitable grain size, thereby changing the fracture mode of the silicon carbide ceramic crystal from a microscopic perspective, from the original transgranular fracture to intergranular fracture, increasing the elongation of the silicon carbide ceramic crystal fracture, and thus improving the toughness and machinability of the silicon carbide ceramic material.
[0011] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. DETAILED DESCRIPTION
[0012] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0013] A first aspect of the present invention provides a method for preparing a high-toughness silicon carbide ceramic material, the method comprising the following steps: Step S1, placing the pickled, washed and dried deposition substrate into a deposition furnace, evacuating the furnace, raising the temperature in the deposition furnace to 900° C. to 1800° C., and raising the pressure in the furnace to 10 kPa to 55 kPa; Step S2, using reducing gas as carrier gas to pass carbosilane gas into the deposition furnace of step S1, the gas flow ratio of the reducing gas to the carbosilane gas is 1:(3-120), adjusting the gas valve to maintain the deposition pressure in the deposition furnace stable at 10 kPa-30 kPa, and stabilizing the deposition temperature in the deposition furnace at 1050° C.-1650° C.; Step S3: After the chemical vapor deposition is completed, the gas in step S2 is stopped, and the high-toughness silicon carbide ceramic material is formed on the surface of the deposition substrate; The grain size of the high-toughness silicon carbide ceramic material is 100nm-1000nm, and the apparent porosity of the high-toughness silicon carbide ceramic material is ≤0.05%.
[0014] The present invention can give the silicon carbide ceramic material relatively excellent microcrack resistance and effectively improve the toughness of the silicon carbide ceramic material by controlling the grain size and apparent porosity of the silicon carbide ceramic material within a suitable range.
[0015] Due to the lack of 5 independent slip systems in the crystals of silicon carbide ceramic materials, plastic deformation cannot be generated by slip to relax stress under the action of external forces, resulting in high brittleness and easy fracture of silicon carbide ceramic materials, which greatly affects the reliability and consistency of the performance of silicon carbide ceramic materials, thereby restricting its further development and application. In addition, due to the valence bond domain of the crystals of silicon carbide ceramic materials, there will be many microcracks in the microstructure, and the presence of microcracks will easily lead to high stress concentration and excessively concentrated tensile stress. When the critical tensile stress value of the ceramic material is exceeded, cracks or defects will expand, eventually leading to brittle fracture. The preparation method of the present invention can change the grain size of silicon carbide ceramic materials to a suitable range, which will change the fracture mode of silicon carbide from a microscopic perspective, from the original transcrystalline fracture to intercrystalline fracture, so the elongation at fracture of silicon carbide increases, and its toughness also increases accordingly.
[0016] Furthermore, the preparation method of the present invention can also regulate the apparent porosity of silicon carbide ceramic materials, and can further change the fracture mode of silicon carbide ceramic materials in microstructure, thereby further improving the toughness of silicon carbide ceramic materials. Apparent porosity refers to the proportion of pores that are clearly visible in a material. In the field of ceramic materials, apparent porosity is usually used to describe the pore structure inside silicon carbide ceramic materials. The smaller the apparent porosity, the denser the internal structure of the silicon carbide ceramic material, and the denser the contact between the grains in the silicon carbide ceramic crystal, so that the grain boundary length between the formed grains is more consistent with the grain size of the silicon carbide ceramic material, thereby further improving the elongation at break of the silicon carbide ceramic material, and further improving its toughness.
[0017] In the present invention, the grain size of the high-toughness silicon carbide ceramic material is controlled within the range of 100nm to 1000nm, which can give the silicon carbide ceramic material a relatively excellent microcrack resistance and effectively improve the toughness of the silicon carbide ceramic material. In a specific embodiment, the grain size of the high-toughness silicon carbide ceramic material can be 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm or a range consisting of any two values. In a preferred embodiment, the grain size of the high-toughness silicon carbide ceramic material is 300nm to 700nm.
[0018] In the present invention, the apparent porosity of the high-toughness silicon carbide ceramic material is ≤0.05%. In a specific embodiment, the apparent porosity of the high-toughness silicon carbide ceramic material can be 0.05%, 0.04%, 0.03%, 0.03%, 0.01% or a range consisting of any two values. In a preferred embodiment, the apparent porosity of the high-toughness silicon carbide ceramic material is 0.01%~0.03%.
[0019] In addition, in order to further improve the toughness of the high-toughness silicon carbide ceramic material, it can be achieved by further measuring and controlling the fracture toughness of the silicon carbide ceramic material within a suitable range. In a specific embodiment, the fracture toughness of the high-toughness silicon carbide ceramic material is 3±0.2 MPa·m 1 / 2 ~8±0.2 MPa·m 1 / 2 In a specific embodiment, the fracture toughness of the high-toughness silicon carbide ceramic material can be 3±0.2 MPa·m 1 / 2 , 4±0.2 MPa·m 1 / 2 、5±0.2 MPa·m 1 / 2 、6±0.2 MPa·m 1 / 2 、7±0.2 MPa·m 1 / 2 、8±0.2 MPa·m 1 / 2 Or a range consisting of any two values. In a specific embodiment, the fracture toughness of the high-toughness silicon carbide ceramic material is 6MPa·m 1 / 2 ~8MPa·m 1 / 2 .
[0020] Furthermore, the toughness of the silicon carbide ceramic material can be further improved by adjusting the density range of the silicon carbide ceramic material. In a specific embodiment, the density of the high-toughness silicon carbide ceramic material is greater than or equal to 3.20 g / cm 3 In a specific embodiment, the density of the high-toughness silicon carbide ceramic material can be 3.20 g / cm 3 、3.21g / cm 3 、3.22g / cm 3 Or a range consisting of any two values. In one specific embodiment, the density of the high-toughness silicon carbide ceramic material is greater than or equal to 3.22 g / cm 3 .
[0021] The preparation method of the present invention adopts CVD chemical vapor deposition method to deposit silicon carbide ceramic material, and can obtain silicon carbide ceramic material with apparent porosity lower than 0.05%, and the silicon carbide ceramic material obtained by the above method is not doped with other metal elements or organic compounds, thereby ensuring that the silicon carbide ceramic material has high purity.
[0022] In step S1 of the present invention, the heating rate when the temperature in the furnace is heated is 5°C / min-10°C / min. Specifically, the heating rate when the temperature in the furnace is heated can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, and the holding time when the temperature in the furnace is heated is 4h~8h. In step S1, the temperature in the furnace is set to 900°C~1800°C, and the heating rate is set to 5°C / min-10°C / min, which can ensure rapid heating in the deposition furnace, which is conducive to accelerating the reaction process, and can also improve the product quality of silicon carbide ceramic materials obtained by chemical vapor deposition.
[0023] In step S1 of the present invention, the pressure increasing rate during the pressure increase in the furnace is 330Pa / min-500Pa / min. Specifically, the pressure increasing rate during the deposition pressure increase is 330Pa / min, 340Pa / min, 350Pa / min, 360Pa / min, 370Pa / min, 380Pa / min, 390Pa / min, 400Pa / min, 410Pa / min, 420Pa / min, 430Pa / min, 440Pa / min, 450Pa / min, 460Pa / min, 470Pa / min, 480Pa / min, 490Pa / min, and 500Pa / min. In step S1, the pressure in the furnace is set to 10kPa~55kPa, and the pressure increase rate is set to 30kpa / min-50kpa / min, which can ensure rapid pressure increase in the deposition furnace, which is beneficial to further accelerate the reaction process, so that the pressure in the furnace is quickly raised to an appropriate level, and can also further improve the product quality of silicon carbide ceramic materials obtained by chemical vapor deposition.
[0024] In step S1 of the present invention, the deposition pressure is increased to 10 kPa~55 kPa; specifically, the deposition pressure is increased in the range of 10 kPa, 15 kPa, 20 kPa, 25 kPa, 30 kPa, 35 kPa, 40 kPa, 45 kPa, 50 kPa, and 55 kPa.
[0025] In the present invention, the step S1 is performed in a pure argon atmosphere.
[0026] In the present invention, the carbosilane hydrocarbon includes at least one of monosilane, disilane, trisilane, methylchlorosilane, dimethylchlorosilane or trichloromethylsilane, preferably trichloromethylsilane.
[0027] In the present invention, the reducing gas includes at least one of hydrogen, methane, ethylene or acetylene, preferably hydrogen.
[0028] In the present invention, the deposition substrate is a carbon-based material and / or a silicon-based material. In a specific embodiment, in step S1, the deposition substrate can be a pure graphite substrate or a silicon carbide substrate.
[0029] In step S2 of the present invention, the gas valve is adjusted to maintain the deposition pressure in the deposition furnace stable at 10 kPa to 30 kPa, and the deposition temperature in the deposition furnace is stabilized at 1050° C. to 1650° C. In a specific embodiment, the deposition temperature in the deposition furnace can be stabilized at 1050° C., 1100° C., 1200° C., 1300° C., 1400° C., 1500° C., 1600° C., and 1650° C. In a specific embodiment, the deposition pressure in the deposition furnace can be stabilized at 10 kPa, 15 kPa, 20 kPa, 25 kPa, and 30 kPa. By adjusting the deposition pressure and deposition temperature in the deposition furnace during the chemical vapor deposition process (i.e., step S2) to be stable within a suitable range, the grain size of the silicon carbide ceramic material can be adjusted to obtain a suitable grain size and apparent porosity, thereby improving the toughness of the silicon carbide ceramic material. More importantly, the chemical vapor deposition method used in the present invention does not introduce any other metal elements or organic compound impurities, so that the obtained silicon carbide ceramic material has a high purity and can better meet the high purity requirements of silicon carbide in the epitaxial growth wafer process. In a specific embodiment, the gas valve is adjusted to maintain the deposition pressure in the deposition furnace stable at 10kPa~20kPa, and the deposition temperature in the deposition furnace is stabilized at 1250℃~1550℃.
[0030] In step S2 of the present invention, the gas flow ratio of the reducing gas to the carbosilane gas is 1:(3-120). In a specific embodiment, the gas flow ratio of the reducing gas to the carbosilane gas can be 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, 1:110, 1:120. In a specific embodiment, in step S2, the gas flow ratio of the reducing gas to the carbosilane gas is 1:(5-50). By further adjusting the gas flow ratio of the reducing gas to the carbosilane gas, the grain size of the silicon carbide ceramic material can be further improved, so as to obtain a suitable grain size and apparent porosity, thereby further improving the toughness of the silicon carbide ceramic material. However, when the gas flow ratio of the reducing gas to the carbosilane gas is greater than 1:3, the amount of reducing gas increases, which will cause the rate of forming the silicon carbide ceramic material by the vapor deposition reaction to become faster, resulting in the inability of some gases inside the ceramic crystal to be discharged smoothly, thereby affecting the apparent porosity of the silicon carbide ceramic material; when the gas flow ratio of the reducing gas to the carbosilane gas is less than 1:120, the amount of carbosilane gas increases and the amount of reducing gas decreases, which will cause the deposition time to become longer and the growth rate of the ceramic crystal to decrease, thereby affecting the formation of the grains and their size range. In a preferred embodiment, in step S2, the gas flow ratio of the reducing gas to the carbosilane gas is 1:(6~20).
[0031] By using the above preparation method, silicon carbide ceramic material is deposited by CVD chemical vapor deposition method, and a silicon carbide ceramic material with an apparent porosity lower than 0.05% can be obtained, and the silicon carbide ceramic material obtained by the above method is not doped with other metal elements or organic compounds, ensuring that the silicon carbide ceramic material has a high purity of 99.9999%, and can ensure that the grain size distribution of the silicon carbide ceramic material is between 100nm and 1000nm, and the density is close to its theoretical density of 3.22g / cm 3 . Moreover, the preparation method of the high-toughness silicon carbide ceramic material provided by the present invention can make the prepared silicon carbide ceramic material form a suitable grain size by adjusting the deposition pressure and deposition temperature in the deposition furnace and the gas flow ratio of the reducing gas and the carbosilane gas on the basis of the chemical vapor deposition preparation process, so that the fracture mode of the silicon carbide ceramic crystal is changed microscopically, from the original transgranular fracture to intergranular fracture, increasing the elongation of the silicon carbide ceramic crystal fracture, and thus improving the toughness and machinability of the silicon carbide ceramic material.
[0032] The second aspect of the present invention provides the use of a high-toughness silicon carbide ceramic material prepared by the method described in the first aspect of the present invention in wafer production or silicon carbide etching.
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Unless otherwise specified, the materials and instruments used in the following examples are commercially available.
[0035] Example 1 For preparing high-toughness silicon carbide ceramic materials, the method specifically comprises the following steps: 1. The graphite substrate was pickled and soaked for 5 minutes, then the graphite substrate after pickling and soaking was ultrasonically washed for 30 minutes, and finally the washed graphite substrate was dried at 200°C for 2 hours; 2. Put the clean and uncontaminated graphite substrate after the above treatment into the deposition furnace for vacuum treatment until the pressure in the furnace drops below 130Pa, and keep the vacuum state in the furnace stable for 30min, start heating at a heating rate of 8°C / min to reach the temperature required for deposition, so that the temperature in the deposition furnace is in the temperature range of 1000°C±100°C, and continuously introduce protective gas argon at 50L / min during the heating process, and make the pressure in the deposition furnace reach the pressure required for deposition and control it in the pressure range of 15kPa±5kPa, and the pressure increase rate at this time is 40kpa / min; 3. When the temperature rises to the required deposition temperature, start to introduce hydrogen and trichloromethylsilane (MTS) into the furnace in a ratio of 1:15, and keep the deposition pressure stable in the pressure range of 10kPa~30kPa during the whole process, and keep the deposition temperature stable in the temperature range of 1050℃~1650℃, and deposit for 6h; 4. After the chemical deposition is completed, stop introducing hydrogen and trichloromethylsilane (MTS), and continue to introduce protective gas argon until the cooling is completed, and the required high-toughness silicon carbide ceramic material is formed on the surface of the graphite substrate.
[0036] Example 2 Group Example 2 was carried out in accordance with Example 1, except that the pressure range required to maintain the deposition pressure in step 3 was changed, as shown below: In Example 2-1, in step 3, the deposition pressure is kept stable at 10 kPa to 20 kPa; In Example 2-2, in step 3, the deposition pressure is kept stable at 20 kPa to 30 kPa.
[0037] Example 3 Group Example 3 was carried out in accordance with Example 1, except that the temperature range to be maintained for the deposition temperature in step 3 was changed, as shown below: In Example 3-1, the deposition temperature in step 3 is kept stable at 1250° C. to 1550° C.; In Example 3-2, the deposition temperature in step 3 is kept stable at 1050° C. to 1250° C.; In Example 3-3, in step 3, the deposition temperature is kept stable at 1550° C. to 1650° C.
[0038] Example 4 Group Example 4 was carried out with reference to Example 1, except that the gas flow ratio of hydrogen and trichloromethylsilane (MTS) introduced into the furnace in step 3 was changed, as shown below: In Example 4-1, the gas flow ratio of hydrogen and trichloromethylsilane (MTS) introduced into the furnace in step 3 is changed to 1:40; In Example 4-2, the gas flow ratio of hydrogen and trichloromethylsilane (MTS) introduced into the furnace in step 3 is changed to 1:10; In Example 4-3, the gas flow ratio of hydrogen and trichloromethylsilane (MTS) introduced into the furnace in step 3 is changed to 1:5; In Example 4-4, the gas flow ratio of hydrogen and trichloromethylsilane (MTS) introduced into the furnace in step 3 is changed to 1:90.
[0039] Comparative Example 1 Comparative Example 1 was carried out in accordance with Example 1, except that the pressure range required to maintain the deposition pressure in step 3 was changed, as shown below: In comparative example 1-1, the deposition pressure in step 3 is kept stable at 0.1 kPa to 5 kPa; In comparative example 1-2, the deposition pressure in step 3 is kept stable at 40 kPa to 50 kPa.
[0040] Comparative Example 2 Comparative Example 2 is carried out with reference to Example 1, except that the temperature range that the deposition temperature needs to be maintained in step 3 is changed. Specifically, the deposition temperature in step 3 is kept stable at 900° C. to 1000° C.
[0041] Comparative Example 3 Comparative Example 3 was carried out with reference to Example 1, except that the gas flow ratio of hydrogen and trichloromethylsilane (MTS) introduced into the furnace in step 3 was changed, as shown below: In comparative example 3-1, the gas flow ratio of hydrogen and trichloromethylsilane (MTS) introduced into the furnace in step 3 was changed to 1:1; In comparative example 3-2, the gas flow ratio of hydrogen and trichloromethylsilane (MTS) introduced into the furnace in step 3 was changed to 1:130.
[0042] Performance test example of silicon carbide ceramic material The silicon carbide ceramic materials prepared in all the above embodiments and comparative examples were subjected to the following ceramic material performance tests, specifically including: (1) Density test and apparent porosity test of silicon carbide ceramic materials Sample preparation: The high-toughness silicon carbide ceramic material samples prepared in the above examples and comparative examples are processed into small pieces of standard size using a cutting machine to ensure that the size is accurate and the surface is flat; Sample drying: Then put the sample into an oven and dry it to constant weight, and record the mass after drying as m1; Immersion measurement: Place the dried sample into a measuring cylinder, add enough water to submerge the sample, and then use a vacuum pump to remove the air in the sample. Place the measuring cylinder containing the sample in an overflow water tank until bubbles no longer escape, and measure the volume of water V1 in the overflow water tank. Sample treatment: Take out the sample after soaking in water, wipe the surface moisture with a damp cloth, and then put it in an oven to dry to constant weight, and record the mass after drying m2; Calculate the density of the sample: According to the formula ρ=m / V, where m is the mass of the sample after drying (m1 or m2) and V is the volume of water (V1), calculate the density ρ of the sample; Calculate the apparent porosity of the sample: According to the formula apparent porosity = (m1-m2) / ρ, where m1 is the mass of the sample after drying, m2 is the mass of the sample after immersion in water, and ρ is the density of the sample, calculate the apparent porosity of the sample; The density and apparent porosity of each group of examples and comparative examples are sorted and recorded in Table 1.
[0043] (2) Fracture toughness test of silicon carbide ceramic materials The high toughness silicon carbide ceramic materials prepared in the above examples and comparative examples were tested for their fracture toughness K using the single edge notched beam method (SENB). Ic :A groove is machined on one side of the silicon carbide ceramic material sample using an internal cutting machine. The depth of the groove c is about 1 / 2 of the test thickness h, and the span L = 20~40mm; the loading rate is 0.05mm / min. Under three-point bending stress, K Ic The calculation formula of the value follows the formula listed in ASTM E 399-74 of the United States: K Ic =P c / b×L / h 3 / 2 ×f(c / h), Where f(c / h)=2.9(c / h) 1 / 2 -4.6(c / h) 3 / 2 +21.8(c / h) 5 / 2 -37.6(c / h) 7 / 2 +38.7(c / w) 9 / 2 , Among them, K Ic :Fracture toughness (MPa·m 1 / 2 );P c : critical load (N); c: groove depth (mm); L: span (mm); b: specimen width (mm); h: specimen height (mm); Finally, the fracture toughness of each group of embodiments and comparative examples were sorted out and recorded in Table 1.
[0044] (3) Grain size measurement of silicon carbide ceramic materials The high-toughness silicon carbide ceramic materials prepared in the above embodiments and comparative examples were measured for several groups of grain sizes using a SEM electron microscope, and the average grain size of the silicon carbide ceramic materials was calculated. The average grain sizes of each group of embodiments and comparative examples were sorted out and recorded in Table 1.
[0045] Table 1 It can be seen from Table 1 that the silicon carbide ceramic material obtained by the preparation method of the high-toughness silicon carbide ceramic material provided by the present invention has excellent fracture toughness, and no impurities of any other metal elements or organic compounds are introduced during the preparation process. It has high purity and can better meet the high-purity requirements of silicon carbide in the epitaxial growth wafer process.
[0046] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing high-toughness silicon carbide ceramic material, characterized in that: The method comprises the following steps: Step S1, placing the pickled, washed and dried deposition substrate into a deposition furnace, evacuating the furnace, raising the temperature in the deposition furnace to 900° C. to 1800° C., and raising the pressure in the furnace to 10 kPa to 55 kPa; Step S2, using reducing gas as carrier gas to pass carbosilane gas into the deposition furnace of step S1, the gas flow ratio of the reducing gas to the carbosilane gas is 1:(5-50), adjusting the gas valve to maintain the deposition pressure in the deposition furnace stable at 10 kPa-20 kPa, and stabilizing the deposition temperature in the deposition furnace at 1250° C.-1550° C.; Step S3: After the chemical vapor deposition is completed, the gas in step S2 is stopped, and the high-toughness silicon carbide ceramic material is formed on the surface of the deposition substrate; The grain size of the high-toughness silicon carbide ceramic material is 100nm-1000nm, and the apparent porosity of the high-toughness silicon carbide ceramic material is ≤0.05%.
2. The method according to claim 1, characterized in that The grain size of the high-toughness silicon carbide ceramic material is 300nm-700nm.
3. The method according to claim 1, characterized in that The apparent porosity of the high-toughness silicon carbide ceramic material is 0.01% to 0.03%.
4. The method according to claim 1, characterized in that The fracture toughness of the high-toughness silicon carbide ceramic material is 3±0.2 MPa·m 1 / 2 ~8±0.2MPa·m 1 / 2 ; preferably 6±0.2MPa·m 1 / 2 ~8±0.2MPa·m 1 / 2 .
5. The method according to claim 1, characterized in that In step S1, the heating rate of the furnace temperature is 5°C / min-10°C / min, and the holding time is 4h-8h; And / or, in step S1, the pressure increasing rate during the pressure increase in the furnace is 330Pa / min-500Pa / min.
6. The method according to claim 1, characterized in that The step S1 is performed in a pure argon atmosphere.
7. The method according to claim 1, characterized in that The carbosilane hydrocarbon includes at least one of monosilane, disilane, trisilane, methylchlorosilane, dimethylchlorosilane or trichloromethylsilane, preferably trichloromethylsilane; and / or, the reducing gas comprises at least one of hydrogen, methane, ethylene or acetylene, preferably hydrogen; And / or, the deposition substrate is a carbon-based material and / or a silicon-based material.
8. The method according to claim 1, characterized in that In the step S2, the gas flow ratio of the reducing gas to the carbosilane gas is 1:(6-20).
9. Use of the high-toughness silicon carbide ceramic material prepared by the method according to any one of claims 1 to 8 in wafer production or silicon carbide etching.
Citation Information
Patent Citations
Silicon carbide ceramic and preparation method thereof
CN116410013A
Method for preparing silicon carbide ceramic material, application and silicon carbide ceramic material
CN117401979A
Method for preparing silicon carbide material, application and silicon carbide material
CN118064864A
IL106864A0
